Liquid and Dense Phase Thermal Conductivity Measurements of CO2 + N2 and CO2 + CH4 Mixtures at Temperatures from 223 K to 308 K and Pressures up to 20 MPa - Kim, D.; Løvseth, S.W.; Arami-Niya, Arash; May, E.F. (2021)
New data are presented for the thermal conductivity for CO2-rich binary mixtures in the liquid and dense phase, for temperatures between 223 and 308 K and pressures up to 20 MPa. Binary mixtures with mole fractions of 5% nitrogen and 5, 10, and 20% methane were investigated. Understanding the fluid properties of CO2-rich mixtures at relevant conditions is important for the deployment of efficient and robust systems for carbon dioxide capture and storage (CCS), but except that for water-rich CO2 + H2O mixtures, no thermal conductivity data on liquid or dense phase mixtures including CO2 are known to be reported prior to this work.